angelsinner100
angelsinner100
03-12-2019
Mathematics
contestada
solve for y
2x - 3y = 1
Respuesta :
PollyP52
PollyP52
03-12-2019
Answer:
y = (2x - 1)/3.
Step-by-step explanation:
2x - 3y = 1
2x - 1 = 3y
y = (2x - 1)/3.
Answer Link
VER TODAS LAS RESPUESTAS ( 69+ )
Otras preguntas
???? Help me please
What was mao zendongs 1966 program to rid China of anti-communist influences called
True or false The latifundia system is considered an obstacle to development in Latin America
"It's more important to be correct than it is to be right."what does it mean?
Why is "Glutathione"considered as a reducing agent?
What’s the answer to this?
Which is not an equation of the line that passes through the points (1, 1) and (5, 5)? A.y - x = 0 B.x - y = 0 C.-x - y = 0
How many consecutive times can a single player hit the ball in volleyball?
Help me please!!!! Please!!!!
1 out of 6 is what percent